2021
DOI: 10.1099/mgen.0.000484
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity of Escherichia coli isolates from backyard chickens and guinea fowl in the Gambia

Abstract: Chickens and guinea fowl are commonly reared in Gambian homes as affordable sources of protein. Using standard microbiological techniques, we obtained 68 caecal isolates of Escherichia coli from 10 chickens and 9 guinea fowl in rural Gambia. After Illumina whole-genome sequencing, 28 sequence types were detected in the isolates (4 of them novel), of which ST155 was the most common (22/68, 32 %). These strains span four of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…We further searched the NCBI web database using blastn , EAKF1_ch3804 was present in one complete genome of E. coli ST9286 from guinea fowl [46] while the other two markers were only found in E. albertii .…”
Section: Resultsmentioning
confidence: 99%
“…We further searched the NCBI web database using blastn , EAKF1_ch3804 was present in one complete genome of E. coli ST9286 from guinea fowl [46] while the other two markers were only found in E. albertii .…”
Section: Resultsmentioning
confidence: 99%
“…E. coli were found to have two-allele sequence types; ST2165 and ST7624. Although ST2165 was previously detected in colistin-resistant E. coli carrying mcr - 1 from residents of long-term-care facilities ( Giufrè et al, 2016 ), it was isolated elsewhere from chickens and store-bought produce ( Reid et al, 2020 ; Foster-Nyarko et al, 2021 ). To our knowledge, this is the first isolation of this sequence type from milk.…”
Section: Discussionmentioning
confidence: 99%
“…In the view of plasmid replicon types, we found that the three E. coli isolates belonging to ST2165 have plasmid replicon types; IncFIA, IncFIB, IncFII, and IncQ1. Likewise, Foster-Nyarko et al (2021) reported that the MDR isolates often co-carried large IncF plasmids like IncFIA, IncFIB, or IncFIC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hoek et al suggested that ST155 and ST10 were most often found in broiler farms (Van Hoek et al, 2018). Not surprisingly, ST155 was the most common in several reports (Foster-Nyarko et al, 2021;Nguyen et al, 2021). In addition, seven ST156 strains were found only on farms, and they may be hosts for the transmission of the carbapenem resistance gene bla NDM , as previously reported (Tang et al, 2019).…”
Section: Similar Amr In Chickens and Farmsmentioning
confidence: 63%